Which is Riskier: OS Diversity or OS Monopoly? - Parnas, David Lorge (Communications of the ACM, 2007)
The article questions whether it is riskier to have operating system diversity or operating system monopoly. The trend of monopoly in the United States corporate computing, which heavily favors Microsoft's "Windows" operating systems, has led to serious security measures. While many believe diversity is the solution to this problem, they somewhat falsely assume that diverse systems will remain functional if any component fails, the components are all fundamentally different, and the components function well together.